Acupuncture modulates group neural activity in patients with post stroke sensory impairment: An fMRI study based on inter-subject correlation and inter-subject functional connectivity - Qian, Xunqi; Zhang, Hua; Peng, Jing; Song, Lei; Lv, Qiuyi; Jia, Weihua; Tan, Zhongjian; Gao, Ying; Zou, Yihuai; Chen, Xing (Brain research bulletin, 2025)
Sensory impairment after stroke has become an important health problem that affects the health and quality of life of patients. Acupuncture is a widely accepted method for stroke rehabilitation. The development of fMRI provides a good platform for the study of neural activity patterns induced by acupuncture, and many studies have found that acupuncture can induce special activation of the brain in stroke patients. We introduced the inter-subject functional connectivity(ISFC) method into the study of acupuncture treatment for sensory impairment after stroke to explore the group effects of acupuncture treatment and the specific mode of action of acupuncture for sensory impairment. In this study, 24 stroke patients with limb numbness and 23 healthy controls were included, and three functional magnetic resonance scans were designed, including resting state, acupuncture task state, and acupuncture-retention state(LI11 and ST36 were used during the task fMRI). The main observation was the connection changes in 50 regions of interest, including the sensory-motor network, central executive network, thalamus, cingulate gyrus, and other brain regions. The findings showed that acupuncture could cause certain patterns of neural activity in the patients. These patterns included a significant rise in ISFC within the sensory-motor network and between the sensory-motor network and the thalamus and the central executive network. When different types of acupuncture were compared, it was found that the first effect of acupuncture was mostly large-scale activation of the sensory-motor network and the thalamus. The second effect, on the other hand, was low-intensity activation in a limited range. In general, this study explored the group mechanism of acupuncture for sensory function rehabilitation after stroke and provided some help for understanding neural activity patterns from a cross-subject dimension. •Focusing on post-stroke sensory impairments, is a clinical challenge.•Using the ISFC algorithm to investigate group-consistent brain responses.•Exploring the immediate effects of acupuncture using task-based fMRI.